2008
DOI: 10.1159/000143388
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Labor in Women with Previous Caesarean Section in a Low Gestational Week

Abstract: Aims: To assess whether vaginal labor after a previous caesarean section in a low gestational week performed by means of a high placed U-section technique could be recommended by obstetricians as a sufficiently safe method of choice for pregnant women. Methods: Of 309 pregnant women with a history of a high placed U-section, 166 (53.7%) met the criteria for the subsequent vaginal delivery and agreed with it. In 78%, vaginal labor started spontaneously and in 22% it was induced due to postterm pregnancy or pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…13 It has been observed that in mice estrogen (17-beta-estradiol-E2) enhances Foxp3 expression in CD25 + T cells both in vitro and in vivo. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] It is a complex molecular response leading to a brief activation of the maternal immune system with an accompanying capacity to restrict this same activation. The beginning of labor is determined not only by the molecular changes in maternal-fetal interface, but most likely also by the activity of the fetal adrenals and related cofactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It has been observed that in mice estrogen (17-beta-estradiol-E2) enhances Foxp3 expression in CD25 + T cells both in vitro and in vivo. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] It is a complex molecular response leading to a brief activation of the maternal immune system with an accompanying capacity to restrict this same activation. The beginning of labor is determined not only by the molecular changes in maternal-fetal interface, but most likely also by the activity of the fetal adrenals and related cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the initiation of labor is accompanied by alterations in the level of maternal immune tolerance toward fetal antigens. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] It is a complex molecular response leading to a brief activation of the maternal immune system with an accompanying capacity to restrict this same activation. 1,18,20,22 An increase in lymphocyte activity during labor has been observed 18 as well as an alteration in the distribution of natural killer (NK) cells (CD56 + CD16 + ) and CD3 positive lymphocytes in the decidua basalis derived from both spontaneous vaginal delivery and cesarean sections.…”
Section: Introductionmentioning
confidence: 99%
“…Binder et al found that in a group of 166 women with a previous high placed U-incision between weeks 25 and 29, 72 percent had a successful vaginal delivery after previous preterm cesarean. 9 Kwee et al found a success rate of 86 percent in a group of 93 women who attempted vaginal delivery after a cesarean between 26 and 34 weeks. 10 Harper et al compared success rates of 508 women who had a first cesarean before 34 weeks to 12 027 women with first cesareans after 34 weeks.…”
Section: Comment Main Findingsmentioning
confidence: 99%
“…6 The role of a previous preterm cesarean has also been investigated as a possible influencer of trial of labor success. [9][10][11] Prematurity in a previous cesarean is presumed to negatively influence vaginal birth success chance. Theoretically, the damage that is done when an incision is made in a preterm, undeveloped lower uterine segment might be more extended in than in a term, fully developed lower uterine segment.…”
Section: Objectivementioning
confidence: 99%